The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014 IEEE International Professional Communication Conference (IPCC) 2014
DOI: 10.1109/ipcc.2014.7020338
|View full text |Cite
|
Sign up to set email alerts
|

Video and course content discussion on Massive Open Online Courses: An exploratory research

Abstract: -This paper deals with the ways in whichMassive Open Online Courses (MOOC) participants use course related forums and the contribution of those forums to the learning experience of their virtual students. We focused on the comparison between, on one hand, video content provided by the course organizers and on the other hand, the content provided by user discussions in the forums. Our methodology frame is based on natural sociological inquiry. Video Lectures, as well as the most active forum threads and their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
2
2
0
1
Order By: Relevance
“…The top contributor wrote 3.3% of the selected posts, and the next in the ranking contributed for 1.6% only (representing 4.9% for the top two contributors). These results are very close to our previous research [56] in which the top 2 contributors were the authors of 5% of all posts and the top 10 contributors authored 7.7%. These numbers are much lower than those from another study that observed that the top 5 contributors were accountable for 43% of posts for one forum, and of 21% of posts for another forum [30] (vs. 8.3% in this research).…”
Section: Active and Self-sustaining Participationsupporting
confidence: 90%
See 3 more Smart Citations
“…The top contributor wrote 3.3% of the selected posts, and the next in the ranking contributed for 1.6% only (representing 4.9% for the top two contributors). These results are very close to our previous research [56] in which the top 2 contributors were the authors of 5% of all posts and the top 10 contributors authored 7.7%. These numbers are much lower than those from another study that observed that the top 5 contributors were accountable for 43% of posts for one forum, and of 21% of posts for another forum [30] (vs. 8.3% in this research).…”
Section: Active and Self-sustaining Participationsupporting
confidence: 90%
“…mMOOCs combine characteristics of both xMOOCs and cMOOCs by providing video lectures given by instructors, accompanied by information exchange and knowledge co-creation through forums led by the participants. This fits Dubosson et al's [56] definition of mMOOC as 'Massive Open Online Courses, which include a mix of formal lectures, passing information in the classic form, and of connectivist exchanges among course participants, with limited course staff intervention, i.e. when less than 10% of all posts are due to staff'.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Por otra parte, otros estudios como Bali et al (2015), Dubosson et al (2015), Blanco et al (2013), Mahajan et al (2019), Smith & Eng (2013 se enfocan en las distinciones de varios tipos de MOOC, de acuerdo al tipo de experiencia de aprendizaje que resulta de sus distintos tipos de diseño instruccional, entre los que se resaltan los xMOOC, cMOOC, los microMOOC, etc.…”
Section: Los Que Están En Decliveunclassified